Analisis Produktifitas Alat Berat pada Pekerjaan Timbunan Proyek Jalan Tol Padang-Sicincin STA.13+300 - 13+900 - Aprillia Rani Hamidah; Puspa Ningrum; Rahmat Tisnawan (Unmuh Babel Press, 2023)
The toll road of Padang - Sicincin uses earth embankments in the construction process. In earth filling work, there is a target that must be met, namely that it must be able to spread and compact the soil by 1,474,809 m3/day, where this volume is the plan to meet the target that has been set. The problem that is currently occurring is that the land for the toll road entrance at STA 13+300 – 13+900 on Jalan Nagari Lubuk Alung has just been acquired in 2022. From the results of a field inspection that took approximately a week, there was a delay in terms of landfill work. in the field. Therefore, it is necessary to research to find out the causes of delays. The focus of this research is to determine the productivity of heavy equipment to determine solutions to catch up with work delays that are occurring. After conducting a review in the field, the results obtained from each heavy equipment were 1,471,150 m3/day (excavator), 1,464,610 m3/day (dump truck), 3,086,070 (bulldozer), and 4,150,272 m3/day. (vibro roller). From the results obtained, the excavators and dump trucks in the field were unable to meet the planned targets. Therefore, the handling efforts carried out are by increasing the number of excavators and dump trucks working in the field. Based on the results of calculations and analysis, to complete the embankment work on time, increase the number of tools by two units for excavators and three units for dump trucks. With this additional simulation, the time required to complete work in the field is 13 days faster than the planned time that had been made.